Elucidating and Mitigating High‐Voltage Degradation Cascades in Cobalt‐Free LiNiO2 Lithium‐Ion Battery Cathodes (Adv. Mater. 3/2022). Issue 3 (21st January 2022) - Park, Kyu‐Young; Zhu, Yizhou; Torres‐Castanedo, Carlos G.; Jung, Hee Joon; Luu, Norman S.; Kahvecioglu, Ozge; Yoo, Yiseul; Seo, Jung‐Woo T.; Downing, Julia R.; Lim, Hee‐Dae; Bedzyk, Michael J.; Wolverton, Christopher; et al.
Abstract : Lithium‐Ion Batteries In article number 2106402, Mark C. Hersam and co‐workers show that lattice oxygen loss plays a critical role in the O3–O1 stacking transition in cobalt‐free LiNiO2 lithium‐ion battery cathodes, which subsequently induces Ni‐ion migration and irreversible stacking faults, microscale electrochemical creep, cracking, and even bending of layers after high‐voltage cycling. By suppressing oxygen evolution, hermetic graphene coatings arrest this degradation cascade, resulting in substantially improved high‐voltage capacity retention.